Kuliah Kerja Nyata (KKN) di Desa Bendungan Kabupaten Kulon Progo Provinsi Daerah Istimewa Yogyakarta - Anindyajati, Adhi (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
The 78th community service (KKN) was conducted in several villages in KulonProgo and GunungKidul Regencies. Authors were in group 87 and stationed in Bendungan Village, KulonProgo. This Community Service Program is focused on developing the potential of villages in the midst of the Covid-19 pandemic. Considering the agricultural background of the Bendungan village residents, programs about the farming, group 87 made a program about the introduction of organic fertilizers and the cultivation of Cavendish Banana. This program can help the local community's economy which is currently declining due to restrictions in carrying out activities amid this pandemic. Cavendish Banana has a fairly high value in the market and is also in great demand from consumers. Apart from developing the village's potential, a program in the form of a pocket book about new normal was arranged. This pocket book contains insights about new normal and new way of life, for example using a mask when traveling, regular hand wash, and always carrying a hand sanitizer